Ethics and the Venezuelan Affirmative (Mayéutica Revista Científica de Humanidades y Artes, 2018)
In this essay the Venezuelan's behavior is studied under the light of ethics. The intention of this study was focused on raising the need to reflect on how ethics can allow the rescue of the Venezuelan affirmative, understanding this from the perspective of the Venezuelan Augusto Mijares. To fulfill this purpose, two opposing situations were analyzed regarding the Venezuelan behavior: creole liveliness and affirmative Venezuelan, in the light of the concept of ethics as individual and collective reflection. Both were analyzed according to the concept of ethics as individual and collective reflection. Thus, the researcher, who is Venezuelan, uses her own experiences and those of people located in her immediate context to expose from a natural hermeneutics what she sees, contrasting it with what is already theoretically established about the behavior of the Venezuelan. In this sense, it was possible to conclude that Venezuelan people heterogeneity makes them to maintain a constant struggle between the affirmative and the negative behavior. The ethical reflection may allow them to return to Venezuelan affirmative and abandon their individuality. Likewise, it is necessary to assume a true commitment of love for the country, for those who live in it and for the surrounding environment, which goes beyond compliance with Venezuelan laws that regulate citizen behavior.
Keywords: ethics; liveliness; Venezuelan affirmative